Women, Communion and Business: Social Transformation from the Economy of Communion - Chavarro Cardozo, Francy Rocio; Dávila Cruz, Carlos Alberto; Arias Vargas, Geyni; Rodriguez Mendez, Ingrid Lorena; Donado Donado, Johanys Liseth; Ávila Chavarro, María Del Mar (LACCEI, 2025)
In the face of growing social inequality and economic exclusion, the Economy of Communion (EoC) is presented as an alternative business model centered on human dignity, solidarity, and the common good. This approach offers a transformative path in which female leadership plays an important role in building more just and sustainable organizations. The overall objective of this research was to analyze the role of women in the strengthening and sustainability of companies that operate under the principles of the EoC, using PADEVI in Timaná, Huila (Colombia) as a case study. The methodology used was qualitative, with a descriptive and exploratory design. Semi-structured interviews, participant observation, and documentary analysis were used, which provided a deeper understanding of organizational dynamics and the role of women within them. Among the results, it was identified that women lead key processes in production, environmental management, and decision-making, strengthening an organizational culture based on equity, cooperation, and community development. In conclusion, it is evident that female participation in EoC companies promotes sustainable and inclusive business models, transforming organizational practices through an ethical and relational approach centered on people. Keywords-- Economy of Communion, Female Leadership, Empowerment, Business Sustainability, Social Equity.